Modelling water-borne infections : the impact of hygiene, metapopulation movements and the biological control of cholera - Njagarah, Hatson John Boscoh (Stellenbosch : Stellenbosch University, 2015)
Thesis (PhD)--Stellenbosch University, 2014.